Analysis of Muslim Customer Loyalty Shopping for Fashion in the Traditional Inpres I Market in Kisaran - Isnaini Harahap; Yenni Samri Juliati Nasution; Chairina Chairina (Budapest International Research and Critics University, 2021)
Customer loyalty is the customer's commitment to a brand, store, or supplier and is reflected in consistent repeat purchases. This customer loyalty can be influenced by product, price, service, and purchasing decisions. The purpose of this study was to determine the direct and indirect influence between product variables, prices, services, and purchasing decisions on the loyalty of Muslim customers shopping for fashion in the traditional Inpres I Market in Kisaran. Method This study uses a quantitative approach with path analysis and a sample of 100 respondents. The results of this study indicate that product, price, and service variables influence purchasing decisions by 66.6% and the remaining 33.4% are influenced by other variables. Whereas product, price, service, and purchasing decision variables affect Muslim customer loyalty in fashion shopping at Traditional Inpres I Market in Kisaran with AA contribution of 70.9% and the remaining 29.1% is influenced by other variables. From the results of the significance test of the indirect effect it was found that there was a significant indirect effect of product, price, and service variables on the loyalty of Muslim customers shopping for fashion through purchasing decisions as an intervening variable in the traditional Inpes I Market in the Range with a 95% confidence level or error rate 5%.